AGENCY PROBLEMS IN MUë •RABAH FINANCING: THE CASE OF SHARIA (RURAL) BANKS, INDONESIA - Muhammad Akhyar Adnan (International Islamic University Malaysia, 2007)
This study examines the agency problems that arise in muèOErabah financing in Indonesian Rural Sharia Banks. The study focus on project attributes, especially those projects that might consider muèOErabah financing, and the attributes of muèOErib who received financing. The research is explorative in nature, combining both qualitative and quantitative approaches. The study found that six attributes were considered relevent from the muèOErabah projects point of view. These include: the prospect of the project, availability of collateral, healthiness of the project, the project’s financial statements, clarity of contract conditions, and conformity of time period. With regard to muèOErib attributes, five characteristics were considered important. They include: business capacity, collateral, muèOErib’s reputation and family background, and their business commitments. Further quantitative analysis has also been conducted to examine those attributes